PHYSIOLOGICAL RESPONSE MYOFASCIAL INDUCTION. PILOT EXPERIENCE (Cuestiones de Fisioterapia, 2004)
The clinical response being analyzed is supported by a detailed study of blood samples taking from a twenty-four-year-old woman who volunteered for myofascial induction. The samples were taken before and after the treatment. The presence of a vegetative response, including symptoms of intense sweating, tachycardia, tachypnea, and also the tendency to manifest different bio-chemical and hematological parameters in the samples, which the patient suffered during the application of the treatment suggests that further study is necessary using a controlled group that is able to quantify the parameters of interest.